2018
DOI: 10.1093/annonc/mdy151.070
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of preoperative, postoperative and perioperative treatments for resectable gastric cancer: A network meta-analysis for the literature of past 20 years

Abstract: fluoropyrimidines, platinum agents, and taxanes. Among them, one patient achieved confirmed partial response, and five pts showed stable disease. The most common treatment-related adverse events (!20% of pts) were rash (60%), anemia (30%), neutropenia (30%), thrombocytopenia (20%), and decreased appetite (20%). The second stage is ongoing. Conclusion: TAS-114 with S-1 showed a preliminary efficacy signal with acceptable safety profiles for heavily pretreated pts with AGC, which would be further confirmed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This provided strong evidence that perioperative chemotherapy methods were also suitable for LAGC treatment in Asian patients. At the same time, meta-analysis suggested that perioperative chemotherapy was superior to traditional adjuvant chemotherapy for LAGC cases [36][37][38][39]. In our study, large retrospectively analyzed data was used through propensity score matching to further explore whether perioperative chemotherapy brought survival benefit to LAGC patients.…”
Section: Discussionmentioning
confidence: 98%
“…This provided strong evidence that perioperative chemotherapy methods were also suitable for LAGC treatment in Asian patients. At the same time, meta-analysis suggested that perioperative chemotherapy was superior to traditional adjuvant chemotherapy for LAGC cases [36][37][38][39]. In our study, large retrospectively analyzed data was used through propensity score matching to further explore whether perioperative chemotherapy brought survival benefit to LAGC patients.…”
Section: Discussionmentioning
confidence: 98%
“…Globally, gastric cancer (GC), also known as stomach cancer, is one of the most common malignancies and the third-leading contributor to cancer deaths, accounting for 8.2% of the total mortality caused by tumors (1). The past several decades have witnessed a substantial decline in the incidence and mortality of GC (2), and there have been breakthroughs in the treatment of early-stage GC (3). However, GC has a high rate of recurrence, metastasis, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The combined modality therapy significantly increases survival in patients with locoregional gastric cancer (5)(6)(7). The most common approach for localized resectable disease (≥cT2 and/or N+) is perioperative chemotherapy.…”
Section: Modality Of the Therapymentioning
confidence: 99%